A Comparison of Creativity‐Relevant Personal Characteristics in Adolescents Across Personality Profiles. (25th May 2020) - Mammadov, Sakhavat
Abstract: The present research investigated personality profiles in early and middle adolescents ( N = 168) and compared the emerged profiles by creative ideation, motivational autonomy, and self‐efficacy in self‐regulation. Cluster analyses revealed three profiles: Resilients, Flexibles, and Averages. The personality types described in the literature were only partially replicable. Resilients had low scores on neuroticism and high scores on the other Big Five traits. Flexibles had high scores on openness and extraversion and average scores on neuroticism, agreeableness, and conscientiousness. Averages had average scores on most personality traits. Resilients and Flexibles scored significantly higher than Averages on creative ideation and autonomous motivation. Resilients had stronger self‐efficacy for self‐regulation than Flexibles and Averages. The findings were discussed in terms of their relevance to personality and creativity literature.